Letter - Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959
013-0112-001 Foreign Office, S.W.1. 31st January, 1940. Dear Sir Walter, You will remember that you wrote to me on the 28th November last about Mrs. Gwendolen Adams [Adams de Puertas], who was imprisoned in Spain. I have now received a report from our Consul-General at Barcelona stating that he has been informed by the police authorities that Mrs. Adams has been provisionally allowed to leave prison. The Consul-General thinks it probable that the release, though provisional at present, may be confirmed in due course. The Consul-General states that he has been in touch with Mrs. Adams' friends and has explained to them that, as she is not a British subject, it is very difficult for him to take any further action in this case. Yours sincerely. Halifax Sir Walter Citrine, K.B.E. 292/946/13/112